Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine how the function [tex]\( f(x) \)[/tex] was transformed to create [tex]\( g(x) \)[/tex], let’s analyze the given data in detail.
We are provided with the following table:
[tex]\[ \begin{array}{|c|c|c|c|} \hline \multicolumn{2}{|c|}{f(x)} & \multicolumn{2}{|c|}{g(x)} \\ \hline x & y & x & y \\ \hline -2 & \frac{1}{9} & -2 & \frac{1}{81} \\ \hline -1 & \frac{1}{3} & -1 & \frac{1}{27} \\ \hline 2 & 9 & 2 & 1 \\ \hline 3 & 27 & 3 & 3 \\ \hline 4 & 81 & 4 & 9 \\ \hline \end{array} \][/tex]
We need to decide on the type of transformation that has been applied to [tex]\( f(x) \)[/tex] to produce [tex]\( g(x) \)[/tex].
### Step-by-Step Analysis:
1. Identify the relationship between the corresponding values of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
- When [tex]\(x = -2\)[/tex]:
[tex]\( f(x) = \frac{1}{9} \)[/tex]
[tex]\( g(x) = \frac{1}{81} \)[/tex]
- When [tex]\(x = -1\)[/tex]:
[tex]\( f(x) = \frac{1}{3} \)[/tex]
[tex]\( g(x) = \frac{1}{27} \)[/tex]
- When [tex]\(x = 2\)[/tex]:
[tex]\( f(x) = 9 \)[/tex]
[tex]\( g(x) = 1 \)[/tex]
- When [tex]\(x = 3\)[/tex]:
[tex]\( f(x) = 27 \)[/tex]
[tex]\( g(x) = 3 \)[/tex]
- When [tex]\(x = 4\)[/tex]:
[tex]\( f(x) = 81 \)[/tex]
[tex]\( g(x) = 9 \)[/tex]
2. Calculate the ratios [tex]\( \frac{f(x)}{g(x)} \)[/tex] to determine the consistency of transformation:
- For [tex]\( x = -2 \)[/tex]:
[tex]\[ \frac{f(-2)}{g(-2)} = \frac{\frac{1}{9}}{\frac{1}{81}} = \frac{1}{9} \times \frac{81}{1} = 9 \][/tex]
- For [tex]\( x = -1 \)[/tex]:
[tex]\[ \frac{f(-1)}{g(-1)} = \frac{\frac{1}{3}}{\frac{1}{27}} = \frac{1}{3} \times \frac{27}{1} = 9 \][/tex]
- For [tex]\( x = 2 \)[/tex]:
[tex]\[ \frac{f(2)}{g(2)} = \frac{9}{1} = 9 \][/tex]
- For [tex]\( x = 3 \)[/tex]:
[tex]\[ \frac{f(3)}{g(3)} = \frac{27}{3} = 9 \][/tex]
- For [tex]\( x = 4 \)[/tex]:
[tex]\[ \frac{f(4)}{g(4)} = \frac{81}{9} = 9 \][/tex]
The ratio [tex]\(\frac{f(x)}{g(x)}\)[/tex] is consistently [tex]\( 9 \)[/tex].
3. Interpretation of the consistent ratio:
Since the ratio of [tex]\(\frac{f(x)}{g(x)}\)[/tex] is [tex]\(9\)[/tex] for all values of [tex]\(x\)[/tex], this indicates that [tex]\(g(x)\)[/tex] is a result of a vertical compression of [tex]\(f(x)\)[/tex] by a factor of [tex]\( \frac{1}{9} \)[/tex].
Vertical compression means that each [tex]\( y \)[/tex]-value of [tex]\( f(x) \)[/tex] is multiplied by [tex]\( \frac{1}{9} \)[/tex] to get the corresponding [tex]\( y \)[/tex]-value in [tex]\( g(x) \)[/tex].
Therefore, the transformation type is:
B. Horizontal or vertical stretch
Since the actual transformation observed is a vertical compression (which is a type of vertical stretch but in the opposite manner), this is the most accurate description among the given options.
We are provided with the following table:
[tex]\[ \begin{array}{|c|c|c|c|} \hline \multicolumn{2}{|c|}{f(x)} & \multicolumn{2}{|c|}{g(x)} \\ \hline x & y & x & y \\ \hline -2 & \frac{1}{9} & -2 & \frac{1}{81} \\ \hline -1 & \frac{1}{3} & -1 & \frac{1}{27} \\ \hline 2 & 9 & 2 & 1 \\ \hline 3 & 27 & 3 & 3 \\ \hline 4 & 81 & 4 & 9 \\ \hline \end{array} \][/tex]
We need to decide on the type of transformation that has been applied to [tex]\( f(x) \)[/tex] to produce [tex]\( g(x) \)[/tex].
### Step-by-Step Analysis:
1. Identify the relationship between the corresponding values of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
- When [tex]\(x = -2\)[/tex]:
[tex]\( f(x) = \frac{1}{9} \)[/tex]
[tex]\( g(x) = \frac{1}{81} \)[/tex]
- When [tex]\(x = -1\)[/tex]:
[tex]\( f(x) = \frac{1}{3} \)[/tex]
[tex]\( g(x) = \frac{1}{27} \)[/tex]
- When [tex]\(x = 2\)[/tex]:
[tex]\( f(x) = 9 \)[/tex]
[tex]\( g(x) = 1 \)[/tex]
- When [tex]\(x = 3\)[/tex]:
[tex]\( f(x) = 27 \)[/tex]
[tex]\( g(x) = 3 \)[/tex]
- When [tex]\(x = 4\)[/tex]:
[tex]\( f(x) = 81 \)[/tex]
[tex]\( g(x) = 9 \)[/tex]
2. Calculate the ratios [tex]\( \frac{f(x)}{g(x)} \)[/tex] to determine the consistency of transformation:
- For [tex]\( x = -2 \)[/tex]:
[tex]\[ \frac{f(-2)}{g(-2)} = \frac{\frac{1}{9}}{\frac{1}{81}} = \frac{1}{9} \times \frac{81}{1} = 9 \][/tex]
- For [tex]\( x = -1 \)[/tex]:
[tex]\[ \frac{f(-1)}{g(-1)} = \frac{\frac{1}{3}}{\frac{1}{27}} = \frac{1}{3} \times \frac{27}{1} = 9 \][/tex]
- For [tex]\( x = 2 \)[/tex]:
[tex]\[ \frac{f(2)}{g(2)} = \frac{9}{1} = 9 \][/tex]
- For [tex]\( x = 3 \)[/tex]:
[tex]\[ \frac{f(3)}{g(3)} = \frac{27}{3} = 9 \][/tex]
- For [tex]\( x = 4 \)[/tex]:
[tex]\[ \frac{f(4)}{g(4)} = \frac{81}{9} = 9 \][/tex]
The ratio [tex]\(\frac{f(x)}{g(x)}\)[/tex] is consistently [tex]\( 9 \)[/tex].
3. Interpretation of the consistent ratio:
Since the ratio of [tex]\(\frac{f(x)}{g(x)}\)[/tex] is [tex]\(9\)[/tex] for all values of [tex]\(x\)[/tex], this indicates that [tex]\(g(x)\)[/tex] is a result of a vertical compression of [tex]\(f(x)\)[/tex] by a factor of [tex]\( \frac{1}{9} \)[/tex].
Vertical compression means that each [tex]\( y \)[/tex]-value of [tex]\( f(x) \)[/tex] is multiplied by [tex]\( \frac{1}{9} \)[/tex] to get the corresponding [tex]\( y \)[/tex]-value in [tex]\( g(x) \)[/tex].
Therefore, the transformation type is:
B. Horizontal or vertical stretch
Since the actual transformation observed is a vertical compression (which is a type of vertical stretch but in the opposite manner), this is the most accurate description among the given options.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.